ACTIVE PERFORMANCE OF DOUBLE SKIN FAÃADE AS AN EFFORT TO CONTROL AIR FLOW ON THE BUILDING ENVELOPE SURFACES - Indra Komala Dewi, Nitih
The Function of building facade as a barrier from direct solar radiation. Hence, Double Skin Facade (DSF) as one of mitigation measures in efforts to reduce the building cooling load. There are various advantages of using this facade system, Double Skin Facade system is expected to optimize the use of energy and reduce the building cooling load, primarily concerned with HVAC system to obtain thermal comfort inside the building. Implementation of active systems in high-rise buildings provide a major role in effort to protect the global environment. In addition, this facade system contribute as an innovation in sustainable buildings, a real action through energy efficiency efforts of building associated with an active building cooling strategy. This study aims to identify the speed performance of air flow that occurs in a cavity of double skin façade. The Identification of speed air flow is focused on the implementation an active response of aperture movement at the outer building skin with spesific angle. Changes in the panel angle of the building envelope is a real time response to climate change in the microenvironment around the building. The research method using Computational Fluid Dynamic simulations (CFD) by using software FloVENT® Version 9.2. This application system aims to analyze the speed movement of air flow in the double facade system, in order to obtain optimum performance on the facades surfaces as building cooling strategy. According to the research results, active double facade performance is considered better than the passive double façade performance. In the air flow conditions of the incident angle 90 degree, the highest performance improvement of air flow with the application of the concept of the double facade active in the climbed period, amounted to 11,28%. On the other side, In the air flow conditions of the incident angle 45 degree, the highest speed airflow performance occurred in the climbed period, performance improvement at 47,56%. The conclusion of this study is active response of building façade through changes in the angle of the building envelope panels enhance the performance speed of the air flow in the air gap of double skin facade.